Cellular and behavioural effects of a new steroidal inhibitor of the N-methyl-d-aspartate receptor 3α5β-pregnanolone glutamate - Rambousek, Lukas; Bubenikova-Valesova, Vera; Kacer, Petr; Syslova, Kamila; Kenney, Jana; Holubova, Kristina; Najmanova, Vera; Zach, Petr; Svoboda, Jan; Stuchlik, Ales; Chodounska, Hana; Kapras, Vojtech; et al. (Neuropharmacology, 2011)
Preclinical studies have demonstrated a considerable role for N-methyl-d-aspartate (NMDA) receptors in excitotoxicity and the concurrent neuroprotective effect of NMDA receptor antagonists. Because NMDA receptors are one of the most widespread receptors in the central nervous system, application of their antagonist often leads to serious side effects ranging from motor impairment to induction of schizophrenic-like psychosis. Therefore, we have initiated development and testing of a novel synthetic NMDA receptor antagonist derived from naturally occurring neurosteroids. 20-oxo-5β-pregnan-3α-yl-l-glutamyl-1-ester (3α5βP-Glu) is a novel synthetic steroidal inhibitor of the NMDA receptor. Our results show that 3α5βP-Glu preferentially inhibits tonically activated NMDA receptors, is able to cross the blood brain barrier, does not induce psychotomimetic symptoms (such as hyperlocomotion and sensorimotor gating deficit) and reduced an excitotoxic damage of brain tissue and subsequent behavioural impairment in rats. In particular, 3α5βP-Glu significantly ameliorated neuronal damage in the dentate gyrus and subiculum, and improved behavioural performance in active allothetic place avoidance tasks (AAPA, also known as the carousel maze) after bilateral NMDA-induced lesions to the hippocampi. These findings provide a possible new therapeutic approach for the treatment of diseases induced by NMDA receptor overactivation.
Keywords: Animals; novorozená zvířata; vztah mezi dávkou a účinkem léčiva; glutamáty; Glutamates; Glutamic Acid; Rats, Long-Evans; pohybová aktivita; Animals, Newborn; neurony; kultivované buňky; Pregnanolone; Neurons; kyselina glutamová; Cells, Cultured; Dose-Response Relationship, Drug; Receptors, N-Methyl-D-Aspartate; potkani Long-Evans; Male; pregnanolon; steroidy; krysa rodu Rattus; receptory N-methyl-D-aspartátu; Motor Activity; Random Allocation; zvířata; mužské pohlaví; Rats; náhodné rozdělení; Steroids